Research on IPv6+ intelligent backbone network technology - Jianguo LIU; Hao QU; Hongming HUANG; Zhidan ZHU (Dianxin kexue)
The China Media Group backbone network is a key infrastructure that connects the headquarters, data centers, hubs/journalists at home and abroad, and “hundreds cities and thousands of screens” across the country, and IPv6+ is the main technical route of the next-generation IP network.The present situation and challenges of the backbone network of the headquarters were mainly analyzed, the principle, advantages and technical characteristics of the core of IPv6+ were introduced, and how IPv6+ technology adapts to the development of broadcast and television services was discussed.Finally, the conception and suggestion of constructing and deploying the next generation broadcast TV backbone network based on IPv6+ were put forward.It provided a new idea to simplify the protocol and speed up the service opening for the future construction of backbone network of radio and television stations.